Samoa Student Assessment : SABER Country Report 2014 - World Bank Group (World Bank, Washington, DC, 2016)
SABER-Student Assessment is a component of the SABER program that focuses specifically on benchmarking student assessment policies and systems. The goal of SABER-Student Assessment is to promote stronger assessment systems that contribute to improvededucation quality and learning for all. Samoa has focused on increasing student learningoutcomes by improving the quality of education in the country. An effective student assessment system is animportant component of efforts to improve education quality and learning outcomes because it provides the necessary information to meet stakeholders’ decision making needs. In order to gain a better understanding ofthe strengths and weaknesses of its existing assessment system, Samoa decided to benchmark this system usingstandardized tools developed under The World Bank’s Systems Approach for Better Education Results (SABER)program. SABER is an evidence-based program to helpc ountries systematically examine and strengthen the performance of different aspects of their education systems.